Does Long-Term Rigid Contact Lens Wear Lead to Acquired Blepharoptosis in Chinese Eyes?. Issue 1 (January 2020) - Yang, Bi; Liu, Longqian; Cho, Pauline
Abstract : Objectives: To determine whether long-term rigid contact lens wear leads to acquired blepharoptosis and whether its development is affected by lens removal methods. Methods: Ninety rigid contact lens wearers (45 rigid gas permeable [RGP] [15–19 years old] and 45 ortho-k [15–40 years old]) who had worn lenses for at least 2 years and 45 spectacle-wearing controls (15–19 years old) were recruited. Margin reflex distance (MRD) and palpebral fissure height (PFH) were measured both subjectively and objectively, but levator function (LF) could only be measured subjectively. For RGP subjects, measurements were made before and 5 min after lens removal. Measurements were compared among the groups and, for rigid lens wearers, between two different lens removal techniques: using a suction holder or by finger-lid manipulation. Results: No significant differences in MRD, PFH, and LF were found between different lens removal techniques in the rigid lens groups ( P >0.05). No significant correlations were found between the parameters of interest and duration of lens wear ( P >0.05). For the RGP group, MRD, PFH, and LF were significantly greater after than before lens removal ( P <0.05), and after lens removal, MRD was significantly smaller than that of the ortho-k and spectacle groups ( P <0.001, P =0.01, respectively) and PFH was significantly smaller than that of the ortho-k group ( P =0.001). However, after lens removal, according to the definition (amount) for ptosis, no subject was diagnosed as having ptosis. Conclusions: Long-term rigid contact lens wear did not lead to acquired blepharoptosis in Chinese eyes. Margin reflex distance, PFH, and LF were not affected by different lens removal techniques.